2014
DOI: 10.4236/ajps.2014.51019
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazolium Test to Evaluate <i>Stizolobium aterrimum</i> Seeds Quality

Abstract: The purpose of this study was to verify the efficiency of methods of pre-conditioning and concentrations of tetrazolium solution in the evaluation of physiological quality of Stizolobium aterrimum seeds. Commercial seeds have passed through the process of accelerated aging for composing lots of 0, 24, 48, 96 and 144 hours, and were submitted to the pre-conditioning: 1) Scarification with sandpaper number 100 and immersion in water at room temperature for 18 hours, 2) Immersion in water at 95˚C and maintained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…parahyba (Fogaça et al, 2011), Annona cherimola Mill. x Annona squamosa L. (Gimenez et al, 2014), Stizolobium aterrimum (Deminicis et al, 2014) y Crambe marítima L. (Guimarães et al, 2015). Lo antes anotado, se ratificó con los resultados obtenidos en la prueba de germinación en cámara germinativa, cuyo porcentaje de plántulas germinadas (85% -95%), no presentó diferencias significativas con los porcentajes de semillas viables estimados mediante los diferentes tratamientos de la prueba bioquímica de tetrazolio (Cuadro 2).…”
Section: Evaluación De Diferentes Concentraciones De Tetrazolio Y Tieunclassified
“…parahyba (Fogaça et al, 2011), Annona cherimola Mill. x Annona squamosa L. (Gimenez et al, 2014), Stizolobium aterrimum (Deminicis et al, 2014) y Crambe marítima L. (Guimarães et al, 2015). Lo antes anotado, se ratificó con los resultados obtenidos en la prueba de germinación en cámara germinativa, cuyo porcentaje de plántulas germinadas (85% -95%), no presentó diferencias significativas con los porcentajes de semillas viables estimados mediante los diferentes tratamientos de la prueba bioquímica de tetrazolio (Cuadro 2).…”
Section: Evaluación De Diferentes Concentraciones De Tetrazolio Y Tieunclassified
“…Temperatures of 35 and 40 ºC were used in the present study in order to decrease the duration of the test; however, the use of higher temperatures did not allow the utilization of tetrazolium solution at 1% in the present study, for promoting intense colorations in the entire extension of the embryo, thus denoting the non-viability of the seeds. Different results were obtained by Deminics et al (2014), who observed that the concentration of the tetrazolium solution at 1.0% for 150 min allowed to evaluate the viability of the lots of velvet bean seeds even at low temperatures, which can be related to some intrinsic characteristic of the species.…”
Section: Resultsmentioning
confidence: 89%
“…Where, SP= Staining Percent, RSS=Red Stained Seeds, TSS= Total Stained Seeds. (Deminicis et al, 2014;Senoz, 2012;Patil and Dadlani, 2009;Leadem, 1984;Copeland and McDonald, 2001 and McDonald and Wilson, 1979) [14,51,41,27,11,32]…”
Section: Sp= [Rss/tss] X 100mentioning
confidence: 99%